A professionally oriented component in foreign language classes of non-linguistic specialties at a university (on the example of legal documents) - Ustelimova, N.A.; Kassenova, A.B.; Mussina, S.K. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
This article is devoted to the peculiarities of working on a professionally oriented component in foreign language classes with students of non-linguistic specialties of higher educational institutions. The relevance of this study lies in the fact that today this direction remains a priority in the methodology and didactics of teaching foreign languages, as it reflects the demands of modern society, namely, the formation and development of a competitive personality capable of quickly adapting to the realities of the modern world of innovation and technology. The purpose of the article is to generalize the concept of professional orientation of a foreign language class at a university in non-linguistic specialties. The authors of the article view in detail on the methodological features of working on legal documents in a foreign language class, consider various types of work that ultimately lead to the formation of intercultural language competence, which is the key goal of the discipline “Foreign Language” at the university. The presented practical material can be taken as an example, adapted to the target groups and integrated into the educational process, and the developed recommendations may be of interest not only to young teachers, but also to experienced methodologists, following which the process of teaching a foreign language with a professionally oriented component can be more interesting and efficient. It was revealed in the process of work that the use of exercises and tasks recommended by the authors, using interactive technologies, makes the process of mastering professional vocabulary entertaining, and also makes it possible for students to use it in further communicative situations.
Университеттегі тілдік емес мамандықтардың шет тілі сабақтарындағы кәсіптік-бағдарлы компонент (заңды құжаттар мысалында)
Профессионально-ориентированный компонент на занятиях иностранного языка на неязыковых специальностях в вузе (на примере юридических документов)
Keywords: professionally oriented component; foreign language; non-linguistic specialties; methods of teaching foreign languages; interactive methods; higher educational institution; innovations and technologies; intercultural language competence